Analisis Problematika dan Tantangan dalam Pelaksanaan Penyuluhan Fardhu Kifayah di Desa Telagah - Mhd Faiz Daffa; Sukma Mulia; Malikul Sholeh Assalim; Asri Salwa Asshafa; Alya Alfarisa (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the implementation of Fardhu kifayah counseling in Telagah Village, Sei Bingai District, Langkat Regency, focusing on the social and cultural problems and challenges faced by the local community. Telagah Village is known for its rich history, strong traditions, and local wisdom that shape its social life. However, in the practice of handling the deceased, several issues remain, including limited community knowledge, lack of regeneration among younger members, inadequate facilities, and the absence of a designated team responsible for the Fardhu kifayah process. These limitations often lead to dependence on a few individuals who possess the necessary skills, creating sustainability concerns in the long run. Furthermore, cultural aspects such as conservative norms, gender role divisions, and deeply rooted customs influence how the community perceives and accepts Fardhu kifayah counseling. The study highlights that successful implementation requires not only technical guidance but also sensitivity to local values and traditions. Strengthening community participation and fostering collaboration between religious leaders and local authorities are essential to ensure the sustainability and effectiveness of Fardhu kifayah education in Telagah Village.